2017
DOI: 10.1038/s41598-017-10025-6
|View full text |Cite
|
Sign up to set email alerts
|

Plasmodium vivax ligand-receptor interaction: PvAMA-1 domain I contains the minimal regions for specific interaction with CD71+ reticulocytes

Abstract: The malarial parasite’s invasion is complex, active and coordinated, involving many low and high affinity interactions with receptors on target cell membrane. Proteomics analysis has described around 40 proteins in P. vivax which could be involved in reticulocyte invasion; few have been studied with the aim of elucidating how many of them establish specific interactions with their respective host cells. Given the importance of knowing which of the parasite’s protein regions are functionally important for invas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(36 citation statements)
references
References 97 publications
4
32
0
Order By: Relevance
“…When Pv RON4 binding to RBC ( m = 34 ± 2.7) was compared with binding to normocytes ( m = 11 ± 1.4), it was observed that the amount of rosettes compared with normocytes became significantly reduced, t test: t (10) = 18.68, p = .001 (Figure b,c). This suggested that Pv RON4 binding to RBC depends on a more immature RBC population, similar to that reported for other P. vivax antigens, such as Pv AMA1 (Arevalo‐Pinzon, Bermudez, Hernandez, Curtidor, & Patarroyo, ), Pv GAMA (Baquero et al, ), and EBP2 (Ntumngia et al, ), whereas Pv DBPRII bound to both RBC and normocytes (Figure c).…”
Section: Resultssupporting
confidence: 81%
See 4 more Smart Citations
“…When Pv RON4 binding to RBC ( m = 34 ± 2.7) was compared with binding to normocytes ( m = 11 ± 1.4), it was observed that the amount of rosettes compared with normocytes became significantly reduced, t test: t (10) = 18.68, p = .001 (Figure b,c). This suggested that Pv RON4 binding to RBC depends on a more immature RBC population, similar to that reported for other P. vivax antigens, such as Pv AMA1 (Arevalo‐Pinzon, Bermudez, Hernandez, Curtidor, & Patarroyo, ), Pv GAMA (Baquero et al, ), and EBP2 (Ntumngia et al, ), whereas Pv DBPRII bound to both RBC and normocytes (Figure c).…”
Section: Resultssupporting
confidence: 81%
“…It has been reported (and also found here) that Pv DBP binding to DARC was susceptible to enzymatic treatment with chymotrypsin (Barnwell, Nichols, & Rubinstein, ), t test: t (4) = 24.4, p = .001 (Figure d). It has also been reported that Pv AMA1 binding was susceptible to neuraminidase and chymotrypsin action (Arevalo‐Pinzon et al, ). Interestingly, it was found here that Pv RON4 interacted with RBC membrane protein receptors susceptible to treatment with the three enzymes evaluated, ANOVA‐Tukey: F (3, 8) = 59, p = .001 (Figure d).…”
Section: Resultsmentioning
confidence: 89%
See 3 more Smart Citations